PREDATION OF AEDES AEGYPTI (LINNEAUS, 1762) LARVAE BY THE BIOREGULATOR GAMBUSIA PUNCTATA (POEY, 1854) UNDER NOCTURNAL CONDITIONS - Argota-Pérez, George (2022)
The objective of the study was to describe the predation of the larvae of Aedes aegypti (Linnaeus , 1762 ) by the bioregulator Gambusia punctata (Poey, 1854) under nocturnal conditions. The study was carried out in a domestic drinking water tank with a capacity of 20 000 L. Ten adult females of G. punctata were placed without feeding for 48 h. An infrared night vision HD video camera (version: DV-FR480) was attached and then, after 72 h, 10 A. aegypti mosquito larvae (L3 and L4) were deposited at night time, 5 min in three replicates. The larvae were tied with a generic black polyester thread and introduced at the same time until contact with the water surface. Recognition time (s) and predation of G. punctata were measured. The average recognition and predation by G. punctata on A. aegypti larvae showed statistically significant differences. The predatory capacity of mosquito larvae by G. punctata was instantaneous under night time conditions. It is concluded that the predatory capacity of G. punctata is natural and its recognition by A. aegypti larvae takes place in seconds, which is essential to maintain the biocontrol of this vector agent.